Forebrain neurocircuitry associated with human reflex cardiovascular control - Shoemaker, J K.; Goswami, Ruma (Frontiers in Physiology, 2015)
Physiological homeostasis depends upon adequate integration and responsiveness of sensory information with the autonomic nervous system to affect rapid and effective adjustments in end organ control. Dysregulation of the autonomic nervous system leads to cardiovascular disability with consequences as severe as sudden death. The neural pathways involved in reflexive autonomic control are dependent upon brainstem nuclei but these receive modulatory inputs from higher centres in the midbrain and cortex. The growth of neuroimaging technologies have allowed closer study of the cortical circuitry related to autonomic cardiovascular adjustments to many stressors in awake humans and have exposed many forebrain sites that associate strongly with cardiovascular arousal during stress including the medial prefrontal cortex, insula cortex, anterior cingulate, amygdala and hippocampus. Using a comparative approach, this review will consider the cortical autonomic circuitry in rodents and primates with a major emphasis on more recent neuroimaging studies in awake humans. A challenge with neuroimaging studies is their interpretation in view of multiple sensory, perceptual, emotive and/or reflexive nature of autonomic responses. This review will focus on those responses related to non-volitional baroreflex control of blood pressure and also on the coordinated responses to non-fatiguing, non-painful volitional exercise with particular emphasis on the medial prefrontal cortex and the insula cortex.